A comparative study on the electron transfer reaction (ETR) of surfactant cobalt(iii) complexes of aliphatic/aromatic ligands in micro heterogeneous media: a thermodynamic approach1. Issue 59 (28th June 2015) - Sugumar, Kannan; Nagaraj, Karuppiah; Murugan, Krishnan Senthil; Thangamuniyandi, Pilavadi; Sakthinathan, Subramanian; Vijayakumar, Pakkiri
<x xml:space="preserve">Abstract</x> The electron transfer reaction between different surfactant cobalt(iii) complex ions and Fe2+ ions in micelles as well as β-cyclodextrin was studied at different temperatures using a spectrophotometry method.